STUDI KELAYAKAN DAN PERANCANGAN STRATEGI PEMASARAN PENDIRIAN USAHA MINI BUFFET TACO DENGAN MEMPERTIMBANGKAN METODE KANSEI ENGINEERING DI SURABAYA - Niko Ferrik; Benny Lianto; Markus Hartanto (Perpustakaan Universitas Surabaya, 2020)
Some examples of street food that have high demand in Surabaya such as kebabs, burgers and crepes. That street foods, kebabs, burgers and crepes have a variety of contents that can be fairly complete. Because of that, the business idea of Mini Buffet Taco is occurred. Mini Buffet Taco is a kind of street food based on Mexican taco food, but in order to differ Mini Buffet tacos with other types of tacos or kebabs, there is a new innovation that the consumers buy not in finished form, but the contents and bread separated, so that when the consumers want to enjoy Mini Buffet Taco, consumers can make taco according to their own desired taste. The layout of the stand should be suited to the emotional needs of the customers, hence the use of kansei engineering method to design the layout of the stand and supported with antrhopometric method to design the layout. This could facilitate operator to ease in serving customer order and shorten the time of serve by designing an ergonomicplacement . From the results of data processing and analysis, for the marketing aspect is very feasible because the effective demand reach to 30,000 people per year. For technical aspect chosen location inside Mall, that is East Cost City. And for the calculation of HPP analysis are obtained selling price Rp.15.150,00 (chicken filling tacos) and Rp.25.650,00 (taco filling cow). For the management aspect required 5 person personnel, where 2 person (owner & chef) are in kitchen and 3 person (head staff, cashier, staff) are in the stand. For financial aspect, show that NPV (Rp331,601,440.74> 0), DPP (1,20 years <5 years) and IRR (100%> MARR = 14,92%) indicates that Mini Buffet Taco business is feasible to establish.